PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR CAMAT BUAY PEMUKA PELIUNG KABUPATEN OKU TIMUR - Ujang Sanusi; Garaika Hamzah; Wahid Eka Saputra (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to determine the effect of organisational culture and leadership on employee job satisfaction, both simultaneously (jointly) and partially. The hypotheses of this study are: 1) There is a positive and significant effect of organisational culture and leadership together on employee job satisfaction; 2) There is a positive and significant influence between organisational culture and employee job satisfaction; 3) There is a positive and significant influence between leadership and employee job satisfaction. This research was conducted at the Buay Pemuka Peliung Sub-District Office, East OKU Regency, using a sample survey research method. The research respondents were 30 employees of the Buay Pemuka Peliung Sub-District Office, East OKU Regency. The instrument used was a questionnaire regarding organisational culture and leadership as the independent variable (independent variable), and a questionnaire regarding employee job satisfaction as the dependent variable (dependent variable). The organisational culture, leadership and job satisfaction questionnaire instruments were validated using the Pearson Product Moment Correlation formula, while the reliability of the instrument was measured using Cronbach's Alpha. Data analysis uses Simple Regression Analysis, Multiple Regression, and Coefficient of Determination (R2). F-test to determine the effect of the two independent variables of organisational culture and leadership simultaneously on employee job satisfaction. Meanwhile, the t-test is used to determine the effect of the two independent variables of organisational culture and leadership partially on employee job satisfaction as the dependent variable. The level of significance used in this study is α = 5%. From the results of the study, it was found that: (1) Simultaneously, there is a significant influence between the independent variables of organisational culture and leadership on the dependent variable of employee job satisfaction where the correlation (R) is 0.747 (2) Partially, there is a significant influence between organisational culture and employee job satisfaction, where the simple correlation coefficient (R) is 0.309, (3) Partially, there is a positive influence between leadership and employee job satisfaction where the simple correlation coefficient (R) is 0.688.